POST STRUCTURALISM - Dr. Roomiya Manzoor and Mr. Sameer Ahmad Dar (International Journal of Research Science and Management, 2017)
Post structuralism is associates with the works of a series of mid 20 th - century French and continental philosophers and critical theorists who came to international prominence in the 1960’s and 1970’s. The term is defined by its relationship to its predecessor, structuralism, an intellectual movement developed in Europe from the early to mid 20 th century which urges that human culture may be understood by means of a structure that differs from concrete reality and from abstract ideas- a third order that mediates between the two. Post structuralist authors all present different critiques of structuralism, but common themes include the rejection of the self-sufficiency of the structures that structuralism posits and an interrogation of the binary opposition that constitute those structures, although many theorists who have been called “post- structuralist” rejected the label.